Pemantauan dan pencirian cuaca-angkasa di kawasan UKM Bangi, Selangor menggunakan penerima GPS - Wayan Suparta; Baharudin Yatim; Mohd Alauddin Mohd Ali (Universiti Kebangsaan Malaysia, 2009)
This research was performed to characterize the variability of weather behavior in the lower and upper atmosphere layers, particularly its dependence on conditions in the troposphere and ionosphere at six different stations over UKM Bangi, Selangor. The measurements are based on short-term monitoring of precipitable water vapour (PWV) in the troposphere and total electron content (TEC) in the ionosphere using ground-based GPS receivers. Data on PWV, TEC and surface meteorological measurements were gathered from 12 November to 7 December 2007. Monitoring Results showed that both profiles of PWV and TEC variations shown diurnal cycle. The PWV and TEC on daily mean generally high, with a value of ~42 mm and ~35 TECU, respectively. It was found that both PWV and TEC variations exhibits influenced by solar activity.